Provably secure dynamic identity-based three-factor password authentication scheme using extended chaotic maps - Islam, SK Hafizul (Nonlinear dynamics, 2014)
With the aim of guaranteeing secure communication through public networks, three-factor password authentication (TF-PWA) scheme plays a key role in many internet applications. Since in TF-PWA scheme, the communicating entities can mutually authenticate each other and generate a shared session key, which will be used for secure exchange of messages in succeeding communication among them. As a result, the TF-PWA schemes gain enormous consideration in recent years. More recently, due to light-weight features of the extended chaotic map, it is also extensively applied in designing of public key encryption, key agreement, image encryption, S-box, hash function, digital signature, password authentication, etc. The aim of this paper was to design a dynamic identity-based three-factor password authentication scheme using extended chaotic map (ECM-TF-PWA) in the random oracle model. The proposed scheme is provably secure based on the intractability assumption of chaotic map-based Diffie–Hellman problem. The informal security analysis gives the evidence that our scheme protects all attacks and provides functionality attributes that are needed in a three-factor authentication system. Besides, the performance discussion shows that our scheme performs better than others in respect of computation and communication cost.